2009
DOI: 10.1186/1471-2407-9-224
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of SFRP5 expression and its inverse correlation with those of MMP-7 and MT1-MMP in gastric cancer

Abstract: BackgroundAs negative regulators in Wnt signaling, Secreted Frizzled-Related Proteins (SFRPs) are downregulated in a series of human cancers; and specifically, some matrix metalloproteinases (MMPs), including MMP-2, MMP-7, MMP-9 and MT1-MMP, are frequently overexpressed in gastric cancer. The aim of this study is to determine the expression status of SFRP5 in gastric cancer and explore the correlation between both the expression of SFRP5 and that of these MMPs in this cancer.MethodsExpression of SFRP5, MMP-2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 37 publications
5
27
0
Order By: Relevance
“…This idea is supported by the cancer literature, which indicates that methylation and inactivation of SFRP5 is associated with ovarian, gastric, breast, and renal cancers as well as myeloid leukemia (58)(59)(60)(61)(62). However, Sfrp5 upregulation is absent in 3T3-L1 adipocytes treated with a demethylating agent (35).…”
Section: Discussionsupporting
confidence: 70%
“…This idea is supported by the cancer literature, which indicates that methylation and inactivation of SFRP5 is associated with ovarian, gastric, breast, and renal cancers as well as myeloid leukemia (58)(59)(60)(61)(62). However, Sfrp5 upregulation is absent in 3T3-L1 adipocytes treated with a demethylating agent (35).…”
Section: Discussionsupporting
confidence: 70%
“…It acts as soluble antagonist of Wnt signaling and is highly expressed in the retinal pigment epithelium, and moderately expressed in the pancreas ("Entrez Gene: SFRP5 secreted frizzled-related protein 5"). Previous studies has identified association of SFRP5 promoter hypermethylation with Acute myeloid leukemia [29], ovarian cancer [30], gastric cancer [31], oral squamous cell carcinoma [32], pancreatic cancer [33] and breast cancer [34]. …”
Section: Discussionmentioning
confidence: 99%
“…Primers for SFRP1, SFRP2 and SFRP5 methylated and unmethylated sequences were described in [14]. A demethylating agent, 5-Aza-2'-deoxycytidine (DAC, 2μmol/L, Sigma) was used to restore SFRP expression in cells with SFRP methylation [9]. In brief, cells were seeded at a density of 3×10 4 cells/cm 2 in a 24 well plate on day 0, and exposed to DAC on day 1, 2, and 3.…”
Section: Methodsmentioning
confidence: 99%
“…The pcDNA3.1 (Invitrogen, Paisley, United Kingdom) SFRP5 vector was made as described in [9]. For transfection experiments, 2×10 5 cells were plated in a 24-well plate 24 hours before transfection.…”
Section: Methodsmentioning
confidence: 99%